Correlation of hs-CRP Levels with Anti-CCP And Rheumatoid Factor Among Clinically Suspected Rheumatoid Arthritis Cases: A Predictor for Early Inflammation? - Kashyap, Bineeta; Goyal, Nisha; Singha, Krishna; Tajuddin, Mohd; Singh, N P; Avasthi, Rajnish (Annals of Pathology and Laboratory Medicine, 2019)
Objective: Despite the wide availability of markers to diagnose the established disease of RA, there is lack of evidence for the suitability of any of these established biomarkers for diagnosing the disease at an early stage of its pathogenesis. Hs-CRP has the potential to be useful as a predictor of early inflammation in clinically suspected RA cases. Methods: 80 patients (40: anti-CCP positive; 40: anti-CCP negative) irrespective of their age and gender were enrolled. RF status and hs-CRP levels were determined in these patients. Correlation of hs-CRP levels with anti-CCP was done. Results: Mean anti-CCP levels among RF positive and negative cases were 410 U/ml and 62.4 U/ml respectively. Among both the groups of anti-CCP positive and negative patients, majority had hs-CRP levels between 50-60 mg/l. Hs-CRP levels were more than 6 mg/l in majority of the suspected arthritis cases irrespective of the anti-CCP or RF status. Mean hs-CRP levels were 50.8 and 43.6 mg/l among anti-CCP positive and negative cases respectively by unpaired t-test. There was no correlation between serum anti-CCP and hs-CRP levels among both anti-CCP negative and positive cases. Conclusions: Hs-CRP when used alone or in combination with other established markers, can aid in the early diagnosis, prediction of course of disease and assessment of response to treatment in RA cases.